Beckmann rearrangement reaction of cyclohexanone oxime in sub/supercritical water: byproduct and selectivity. Issue 32 (10th April 2015) - Li, Yang; Wang, Kai; Qin, Kang; Wang, Tao
<x xml:space="preserve">Abstract</x> The byproduct acetamide was proposed for the Beckmann rearrangement reaction of cyclohexanone oxime in subcritical and supercritical water.